2015
DOI: 10.5935/0034-7280.20150030
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis prevalence in an university hospital

Abstract: The authors declare no conflicts of interest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Researchers conducted a study in which they observed that the mean time to onset of symptoms of postoperative complications was 6 days (when assessed from 1 to 30 days) for cataract surgery (Coelho, Souza, & Tanure, 2015). Other authors stated that the estimated time for postoperative complications after cataract surgery is typically up to 3 days after the surgical procedure (Hayashi, Sasaki, Manabe, & Hirata, 2018; Luz, Cvintal, Silva, & Padoveze, 2018; Nizamani, Bhutto, & Talpur, 2013) and may occur until the 30th day after (Cetinkaya, Cetinkaya, Dadaci, & Acir, 2016; Mattos, Saraiva, Angotti-Neto, & Passos, 2013; Råen, Sandvik, & Drolsum, 2013; Toyama, Ueta, Yoshitani, Sakata, & Numaga, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers conducted a study in which they observed that the mean time to onset of symptoms of postoperative complications was 6 days (when assessed from 1 to 30 days) for cataract surgery (Coelho, Souza, & Tanure, 2015). Other authors stated that the estimated time for postoperative complications after cataract surgery is typically up to 3 days after the surgical procedure (Hayashi, Sasaki, Manabe, & Hirata, 2018; Luz, Cvintal, Silva, & Padoveze, 2018; Nizamani, Bhutto, & Talpur, 2013) and may occur until the 30th day after (Cetinkaya, Cetinkaya, Dadaci, & Acir, 2016; Mattos, Saraiva, Angotti-Neto, & Passos, 2013; Råen, Sandvik, & Drolsum, 2013; Toyama, Ueta, Yoshitani, Sakata, & Numaga, 2018).…”
Section: Discussionmentioning
confidence: 99%